2022
DOI: 10.1108/jfrc-10-2021-0082
|View full text |Cite
|
Sign up to set email alerts
|

Does board-level employee representation impact firms’ value? Evidence from the European countries

Abstract: Purpose Using, for the first time, a sample of European listed firms from 30 countries with different legal regimes of board-level employee representation (BLER), the purpose of this paper is to examine the impact of BLER on firms’ value of European public companies, where employee representation is voluntary or imposed by law depending on the country of origin. Design/methodology/approach Using a difference-in-differences approach and a matching procedure, the authors analyze the impact of BLER on firms' va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…They believe that co-deciding can be voluntary if employees are able to bring added value to the table. An attempt to verify this thesis has recently been undertaken by authors in research conducted in 30 countries (Silva et al, 2022). They have found that in countries without BLER legislation, companies where employee representatives were voluntarily members of the company's governing bodies achieved favourable economic results.…”
Section: Literature Reviewmentioning
confidence: 92%
“…They believe that co-deciding can be voluntary if employees are able to bring added value to the table. An attempt to verify this thesis has recently been undertaken by authors in research conducted in 30 countries (Silva et al, 2022). They have found that in countries without BLER legislation, companies where employee representatives were voluntarily members of the company's governing bodies achieved favourable economic results.…”
Section: Literature Reviewmentioning
confidence: 92%